ANTIMICROBIAL DELIVERY SYSTEM FOR ROOF COVERINGS - BRYSON, MICHAEL L; KLEINLAUTH, PHILLIP; WILSON, PAUL G; KIIK, MATTI (2011)
The disclosed principles provide a roofing product and related methods of manufacturing having antimicrobial properties. The antimicrobial properties are provided by an antimicrobial delivery system including antimicrobial materials compounded, e.g., mixed together and melted, with polymeric materials. The antimicrobial delivery system is applied to roof covering material during the production process. The roof covering material may be sheets, shingles, panels, or roll stock.